INTAKE OF NUTRIENTS, STUNTING AND ANEMIA IN THE ELEMENTARY SCHOOL CHILDREN IN TRADISIONAL GOLD MINING POBOYA, PALU - bohari, bohari; rahman, nurdin; indriany, indriany (Tadulako University, 2017)
Background & Objective: School-aged children are a group of children who are vulnerable to unbalancednutritional intake so that the risk of high rates of growth failure in children. To analyze the correlation ofprotein, essential amino acids, folic acid and iron intake with z-score height according to age andhemoglobin level. Material and Method: A quantitative research using cross-sectional research design. Thepopulation is all elementary school students class I - V at SDN Poboya is 220 students. The sample sizeobtained by Slovin formula calculation is 69 students. Data of protein, amino acids, folic acid and iron intakewere measured using SQ-FFQ questionnaire. Stunting is measured using a height measuring instrument andWHO Anthro application, hemoglobin levels using the GCHb EasyTouch tool. Analysis data of univariateand bivariate. Results: Average protein intake (66.3 ± 1.6 g), amino acid (isoleu-cine = 3.1 ± 0.7; leucine =5.3 ± 1.3; lysine = 4.4 ± 1.2; methio-nine = 1.5 ± 0.4), iron (7.7 ± 2.1), and folic acid (150.6 ± 45.4). Theincidence of stunting is 15.9% and anemia is 33.3%. Intake of proteins, amino acids, iron, and folic acid hadno significant correlation with the value of Z-Score Height According to Age (p> 0.05) whereas withhemoglobin levels have a significant correlation (p < 0,05). Conclusion: Intake of nutrients that are still lessthan the AKG in children are amino acids, folic acid and iron. The intake of nutrients that correlatedpositively with hemoglobin levels were proteins, amino acids, folic acid, and iron.